Dysphagia in oropharyngeal squamous cell carcinoma in perspective. Issue 16 (3rd May 2017) - Koch, Wayne
Abstract : Swallowing problems occur universally in patients who are treated for oropharyngeal cancer. Transoral robotic surgery contributes to immediate problems, but its impact on long‐term functional outcomes remains uncertain. See also pages 3132‐40.